Cost-effectiveness of MR-mammography as a solitary imaging technique in women with dense breasts: an economic evaluation of the prospective TK-Study - Froelich, Matthias F.; Kaiser, Clemens G. (European radiology, 2021)
To evaluate the economic implications of our previous study on the use of MR-mammography (MRM) as a solitary imaging tool in women at intermediate risk due to dense breasts.